Proses Komunikasi dalam Penyuluhan Pertanian Program System of Rice Intensification (SRI) - Salman Ali Rusdy; Aryo Fajar Sunartomo (Jurnal KIRANA, 2020)
Communication and development are two things that are very closely related. Agricultural extension activities are one of the facilitating factors for agricultural development. Agricultural extension activities are a communication process where field agricultural extension agents become information sources and farmers as recipients of information. The research objective is to identify the communication process in delivering information about agricultural extension. The study was conducted using qualitative methods. Research location in Rowotengah Village, Sumberbaru District, Jember Regency, East Java. Determination of informants was determined by purposive sampling. Data collection methods used are observation, interviews and documentation. Data analysis used the Miles and Huberman model, namely data reduction, data presentation and conclusion drawing. Test the validity of the data using source triangulation. The results showed that communicators in agricultural counseling were field agricultural extension workers, farmers and pesticide formulator officers. The message conveyed in agricultural extension is the SRI planting system method which includes field schools, organic fertilization, and the manufacture of MOL. The communication channels used are interpersonal channels including face to face, cellphone, and group meetings. The targets of agricultural counseling are group leaders and members of farmer groups. The effect of communication received from the delivery of information on agricultural extension includes cognitive effects, affective effects and conative effects. Keywords : agricultural extension, SRI Program, communication process